Principles of Package Development - Griffin, Roger C. author. aut Link
XII, 378 p.
Keywords: Since the first edition of "Principles of Packaging Development" was published, the packaging industry has undergone many profound changes. These have included the virtual elimination of cellophane and its replacement with oriented polypropylene as a carton overwrap, fluid milk in blow-molded HDPE bottles, PET beverage bottles, cookie bags and cartons lined with polyolefin coextrusions instead of waxed glassine, and bread in reclosable polyolefin and coextruded film bags. New phrases have also worked their way into the lexicon of the practic ing packaging technologist, such as "child resistance" and "tamper evident. " This most popular text on packaging demanded updating. How these phrases and ideas have affected the industry in the 1980s and how they will probably alter its course in the future are treated. New concepts of packaging system planning and forecasting tech niques are intruding into package management, and new chapters will introduce them to the reader. The years have added a certain degree of maturity to the packaging industry. Not only have the original authors broadened their per spectives and changed professional responsibilities, we have also in cluded a third co-author, Dr. Aaron L. Brody, whose experience in the industry, academic background, and erudite insights into the very na ture of packaging have added an unparalled degree of depth to this book. We would like to thank David L.